AB0599 CLINICAL MANIFESTATIONS OF BEHÇET'S SYNDROME IN A LARGE COHORT OF ITALIAN PATIENTS: FOCUS ON GENDER DIFFERENCES. (June 2019) - Leccese, Pietro; Lascaro, Nancy; Padula, Maria Carmela; Carbone, Teresa; Padula, Angela; D'angelo, Salvatore
Abstract : Background: Behçet's syndrome (BS) is a chronic multisystemic inflammatory disorder classified among primary vasculitis. BS clinical hallmarks are mucocutaneous manifestations which include oral aphtosis (OA), genital ulcers (GU) and a wide spectrum of skin lesions. Other BS features include ocular inflammation, articular, gastrointestinal, vascular and neurological involvement. Some evidences suggest that in non endemic regions the disease tend to be less severe and women seem to be more commonly affected [1-3]. Objectives: The aim of this study was to investigate the clinical phenotypes of Italian BS patients with respect to gender and HLA-B51 status. Methods: We retrospectively evaluated 324 Italian patients (185 males and 139 females), seen consecutively at Rheumatology Institute of Lucania (IReL) from 1 st January 2000 to 31 th December 2017. Demographics, clinical features during follow-up and HLA status were obtained from a review of medical records. The analysis was limited to patients fulfilling the ISG criteria. Results: 324 BS patients were identified in our database. 39 (17 males and 22 females) were excluded because did not satisfied ISG criteria and 285 (168 males and 117 females) resulted eligible for the present study. Results are summarized in table 1 . We found statistically significant differences in papulopustolar lesions, posterior uveitis and deep venous thrombosis (DVT), which occur more frequently in males compared with females (83.3% versus 46.2%, 37% versus 18.8% and 8.3% versus 0.9% respectively; p<0.01). Erythema nodosum (EN) (59% versus 41, 1%, p<0, 01), arthralgia (52.1% versus 31.5%, p<0.01) and intestinal involvement (11.3% vs 21.4% p<0.05) resulted more frequent in females compared with males. No differences were found in HLA status (M 67.9% vs F 61.5%). Conclusion: In our cohort of Italian BS patients the disease results slightly more prevalent in males. Gender-related differences were observed for posterior uveitis, DVP and papulopustolar lesions which are more frequent in males, whereas EN-like lesions, arthralgia and intestinal involvement are more frequently observed in females. These data confirm that BS tend to be less aggressive in Italian female patients. No sex-differences were observed in HLA-B51 status. Reference: [1] Leccese P, et al. Curr Opin Rheumatol.2017;29(1):12-16. [2] Hatemi G, et al. Clin Exp Rheumaology.2016;34 Suppl 102:10-22. [3] Pipitone N, et al. Clin Exp Rheumatol.2004;22(6 Suppl 36):S46-51. Acknowledgement: Many thank to Professor Olivieri for his teachings Disclosure of Interests: Pietro Leccese: None declared, Nancy Lascaro: None declared, Maria Carmela Padula: None declared, Teresa Carbone: None declared, Angela Padula Speakers bureau: Lilly Italia EMS, Salvatore D'Angelo: None declared